The role of bacterial consortium as bioactivator to stimulate production and suppress grain rot disease and bacterial leaf blight in rice - Sahlan, Fadyah Khamila; Ayu Eka, Nur Fadhillah; Junaid, Muhammad; Hardina, Nur; Nurmujahidin; Kuswinanti, Tutik; Patandjengi, Baharuddin (Universitas Lampung, 2023)
Burkholderia glumae and Xanthomonas oryzae pv. oryzae are the primary causes of bacterial disease in rice, capable of reducing production and posing a threat to food availability. This research aims to assess the efficacy of a consortium of five bacteria contained in Mikrobat as bioactivators. The goal is to enhance rice yields, mitigate the severity, and suppress grain rot disease and bacterial leaf blight in rice. The research employed a split-plot design encompassing 12 treatment combinations replicated three times. The experimental setup involved two factors: the main plot consisted of rice varieties-Ciherang, Inpari 4, and Trisakti-while the subplots represented types of bioactivators-Mikrobat, EM4, Trichoderma asperellum, and a control. Results demonstrated Mikrobat’s positive impact compared to the control, with an average of 17.37 productive tillers and higher yields than other bioactivator treatments. Notably, Mikrobat exhibited 50.04% spikelets per panicle and a 1000-grain weight of 19.77 g. The severity of disease with Mikrobat treatment was notably lower than with EM4 and T. asperellum, featuring 4.20% for grain rot disease and 4.41% for bacterial leaf blight. This was significantly different from the control, which showed severity rates of 9.94% for grain rot disease and 7.75% for bacterial leaf blight. Among the three tested varieties, Ciherang demonstrated the best response, displaying higher resistance to both tested diseases. The varietal treatments did not significantly differ from each other. Although Mikrobat’s effects were not significantly distinct from EM4 and T. asperellum, its usage still reduced the severity and suppression of grain rot and leaf blight diseases